La correspondència de les diputacions generals com a font per a l'estudi de les identitats nacionals. Una aproximació. - PAÑOS, JAVIER FAJARDO (Scripta)
The paper introduces the Diputació del General of Principality of Catalonia and Kingdom of Valencia's correspondence as a source for national identies' studies into the context of the Catalan Civil War (1460-1472). Specifically, throught epistolar relationship, this work analizes the identitary discourse used by the catalan and valencian diputies during the main events of the war, with special attention of identitari perception on not only from catalan and valencian oligarchy but also from Kingdom of Mallorca.